3(1-4x)-1(2X-1)2(2)=7

Simple and best practice solution for 3(1-4x)-1(2X-1)2(2)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-4x)-1(2X-1)2(2)=7 equation:


Simplifying
3(1 + -4x) + -1(2X + -1) * 2(2) = 7
(1 * 3 + -4x * 3) + -1(2X + -1) * 2(2) = 7
(3 + -12x) + -1(2X + -1) * 2(2) = 7

Reorder the terms:
3 + -12x + -1(-1 + 2X) * 2(2) = 7

Reorder the terms for easier multiplication:
3 + -12x + -1 * 2 * 2(-1 + 2X) = 7

Multiply -1 * 2
3 + -12x + -2 * 2(-1 + 2X) = 7

Multiply -2 * 2
3 + -12x + -4(-1 + 2X) = 7
3 + -12x + (-1 * -4 + 2X * -4) = 7
3 + -12x + (4 + -8X) = 7

Reorder the terms:
3 + 4 + -8X + -12x = 7

Combine like terms: 3 + 4 = 7
7 + -8X + -12x = 7

Add '-7' to each side of the equation.
7 + -8X + -7 + -12x = 7 + -7

Reorder the terms:
7 + -7 + -8X + -12x = 7 + -7

Combine like terms: 7 + -7 = 0
0 + -8X + -12x = 7 + -7
-8X + -12x = 7 + -7

Combine like terms: 7 + -7 = 0
-8X + -12x = 0

Solving
-8X + -12x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '12x' to each side of the equation.
-8X + -12x + 12x = 0 + 12x

Combine like terms: -12x + 12x = 0
-8X + 0 = 0 + 12x
-8X = 0 + 12x
Remove the zero:
-8X = 12x

Divide each side by '-8'.
X = -1.5x

Simplifying
X = -1.5x

See similar equations:

| 5(9+4n)-7n=3(6n-6)-2n | | 4x-11=13-2x | | x+14=2x+1 | | 3=3+4x | | 3x+44+(x+20)=180 | | -14=2(6-k)+6(7+6k) | | 24-27(9+6n)=267 | | 3x-10=65 | | 1000x-2000=2000-1000x | | 2000x-4=8-3000x | | 179(x+9)=-289 | | w+41=0 | | 140x-7=240x-8 | | 490x-406=308x-820 | | 498x-403=290x-816 | | 498x-403=29x-500 | | 498x-403=29x-816 | | 9x-4(x-3)=72 | | 100x-200=400-100x | | 290-42x=322-4x | | m-6=-10-3m | | 290-41x=311-4x | | 3x-3=3x-3 | | 41-7x=9x-55 | | -2(3-y)+8-5(2y-1)=3y | | 3+5x=8+4x | | 3d+4=2+3d-.5 | | 23x-52-17x=80-6x-12 | | -4(2w-5)=3w-13 | | 4.5x+3.4=1.5x-2.6 | | 8(3+n)-2(6n+5)= | | -x(7x-1)+8(1+8)= |

Equations solver categories